(3eNJUQ ef cJGH GdhGVM aj GdQei HGdfTGHIs - (3YHO GdQMef Hf CMeO GdWHQjs
(3ChdgG (B:s
(3bGd CHh LYaQ eMeO Hf MQjR GdWHQi QMeg Gddg (B: (3GdMeO ddg QH GdYGdejf gPG cJGH CdafGg ai GdQei HGdfTGHI GdWhjdI hGdbUjQI s
(3BNQgG (B:s
(3hgj JYed ef GdOQhY hJYed GeJdGA GdMSHGfI Ohf SYI GdeLQi bdjdkG hHGddg GdJhajb gPG BNQ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(32 / 2 (3b(B) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs